2017
DOI: 10.1530/eje-17-0111
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating between virilizing ovary tumors and ovary hyperthecosis in postmenopausal women: clinical data, hormonal profiles and image studies

Abstract: In this group of patients, the main features contributing to the differential diagnosis of VOT and OH were serum levels of testosterone and gonadotropins and the presence of an ovarian nodule identified on the MRI. Although the association of clinical, hormonal and radiological features contributes to the differential diagnosis of these two conditions, histopathological analysis remains the gold standard for the diagnosis of ovarian hyperandrogenism in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
0
38
0
3
Order By: Relevance
“…However, the study by Yance et al . (12) demonstrated best discriminating FSH level as 22.3 mIU/mL but again compromising the sensitivity to 77%. Use of this cut-off would have missed both of our patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the study by Yance et al . (12) demonstrated best discriminating FSH level as 22.3 mIU/mL but again compromising the sensitivity to 77%. Use of this cut-off would have missed both of our patients.…”
Section: Discussionmentioning
confidence: 93%
“…Study done by Hai Yan Zhang found that the median level of testosterone concentration was as high as 9.75 ± 6.86 ng/mL (range 3.6–21.9 ng/mL) before excision of VOT and reduced to normal level with in the 10 days after the surgery (11). Although lower serum total testosterone cut-offs (1.0–1.4 ng/mL) (12) have been suggested to differentiate OH and VOT in postmenopausal women, a recent study by Yance et al . questioned diagnostic accuracy of these cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Once an adrenal source of T excess has been ruled‐out, differentiating between OH and VOTs may be challenging. The initial plausible notion that patients with VOTs present with rapid virilization has not been substantiated so far . In a case‐control series, there was no significant difference in duration from onset of symptoms to diagnosis, ranging from 4 to 126 months, when comparing patients with OH and VOTs .…”
Section: Diagnostic Approach To Severe Postmenopausal Hyperandrogenismmentioning
confidence: 95%
“…The initial plausible notion that patients with VOTs present with rapid virilization has not been substantiated so far . In a case‐control series, there was no significant difference in duration from onset of symptoms to diagnosis, ranging from 4 to 126 months, when comparing patients with OH and VOTs . The only discriminatory virilizing signs between the 2 groups were deepening of the voice and muscular hypertrophy, ascertainment of which in clinical practice relies heavily on patients’ subjective assessment and, possibly, comparison of serial photographs.…”
Section: Diagnostic Approach To Severe Postmenopausal Hyperandrogenismmentioning
confidence: 99%
“…Це стан, який характеризується лютеїнізацією строми яєчників, високими рівнями ЛГ, гіперінсулінемією та інсулінорезистентністю. Причини яєчникового гіпертекозу залишаються невідомими [47]. Провідна роль в його патогенезі належить високим рівням гонадотропінів, зокрема ЛГ, що призводить до гіперплазії стромальних яєчникових клітин.…”
Section: яєчниковий гіпертекоз (стромальний текоматоз яєчників)unclassified